Protective Effect of Bergapten against Human Erythrocyte Hemolysis and Protein Denaturation In Vitro - Douglas Bosco Aidoo; Daniels Konja; Isaac Tabiri Henneh; Martins Ekor (International Journal of Inflammation)
Bergapten, a furocoumarin found in many medicinal plants, is used for the management of various conditions. The present in vitro study evaluated the ability of bergapten to prevent human erythrocyte hemolysis and protein denaturation. Bergapten administered at 10, 30, and 100 μg/ml exhibited a significant concentration-dependent protection on the erythrocyte membrane exposed to hypotonicity and heat-induced hemolysis. The concentration at which bergapten inhibited 50% of the cells from hemolysis (IC50) was determined on a dose-response curve, plotted as logarithmic (concentration) against percentage inhibition, keeping the hemolysis produced within the control group at 100%. Bergapten treatment produced an IC50 value of 7.71 ± 0.27 μg/ml and 4.23 ± 0.42 μg/ml for hypotonicity and heat-induced hemolysis, respectively. Diclofenac sodium at similar concentrations produced an IC50 value of 12.22 ± 0.30 μg/ml and 9.44 ± 0.23 μg/ml in the hypotonicity and heat-induced hemolysis, respectively. The ability of bergapten to inhibit protein denaturation was studied as part of an investigation on its mechanism of action. The results showed a significant concentration-dependent reduction in protein denaturation. When administered at 10, 30, and 100 μg/ml, bergapten produced a concentration-dependent reduction in albumin denaturation. Bergapten inhibited protein denaturation with IC50 values of 5.34 ± 0.30 μg/ml and 12.18 ± 0.20 μg/ml in the heat-treated egg albumin and bovine serum albumin denaturation experiments, respectively. Diclofenac sodium (10, 30, and 100 μg/ml) exhibited a similar protection against heat-treated egg albumin and bovine serum albumin denaturation experiments with IC50 values of 8.93 ± 0.17 μg/ml and 12.72 ± 0.11 μg/ml, respectively. Taken together, data from this study show that the pharmacological properties of bergapten may in part be related to its membrane-stabilizing and antidenaturation properties.